Circular Cardboard Cutter Design for Piggy Bank MSME Production: Desain Pemotong Karton Bulat untuk Produksi Celengan oleh UMKM - Wibawansyah, Sulung; Mulyadi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Micro, small, and medium enterprises require efficient production tools to support increasing demand and operational sustainability. Specific Background Manual cutting processes in piggy bank production are time-consuming and limit productivity. Knowledge Gap Existing practices lack simple, efficient, and affordable cutting tools specifically designed for MSME-scale production. Aims This study aims to design a circular cardboard cutting tool using an electric motor and to determine the most suitable design concept. Results The selected concept A demonstrates a maximum von Mises stress of 5.433 MPa, maximum displacement of 0.041 mm, and a safety factor of 43, indicating structural safety. The design provides high efficiency and ease of manufacturing. Novelty This study integrates morphological chart-based concept generation with structural simulation for MSME-oriented tool design. Implications The proposed design offers a practical and affordable solution to support production capacity improvement in small-scale piggy bank manufacturing. Keywords: MSME Production, Morphological Chart, Product Design, Cardboard Cutting, Mechanical Simulation Key Findings Highlights Selected configuration meets structural safety requirements Concept evaluation identifies most feasible design alternative Tool structure supports stable operational performance